Pengaruh Pendekatan Accelerated Learning melalui Metode Whole Brain Teaching terhadap Hasil Belajar Fisika SMP Materi Usaha dan Pesawat Sederhana - Febri Ekasari; Effendi Effendi; Siti Anisatur Rofiqah (U-Teach: Journal Education of Young Physics Teacher, 2020)
This study aimed to determine whether there is an effect on the results of learning physics uses the accelerated learning approach with the whole brain teaching method on work and simple plane material at SMP Terpadu Pondok Pesantren Nurul Huda, 2020/2021 academic year. This research was a quantitative research. The population in this study were students of class VIII at the Nurul Huda Integrated Junior High School, which consisted of 5 classes. The sample in this study was carried out randomly. The experimental class conducted learning by applying the accelerated learning approach through the whole brain teaching method,while the control class used conventional methods. Data collection techniques to determine student learning outcomes using test instruments, and testing the hypothesis using the t-test. Based on the test results, the experimental class average score is 73 and the control class average is 71. The t test results show that tcount = 2.53 and ttable = 1.68, so that H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant effect or difference in the average score between the class with accelerated learning approach with the whole brain teaching method and the class with conventional methods.